Functionally-graded shape memory polymer board - Kohei TAKEDA (The Japan Society of Mechanical Engineers, 2016)
If the shape memory polymer is applied to actuators, the novel intelligent shape memory actuators can be developed. The development of the functionally-graded shape memory polymer board was investigated for the development of the new actuators. The results obtained are summarized as follows. (1) Based on the shape recovery and recovery stress, the temperature-dependent multistep actuation can be obtained by using the shape memory polymer sheets and foams with various glass transition temperatures in the shape memory polymer actuators. (2) The functionally-graded shape memory polymer board composed of shape memory polymer sheets and foams, showing the similar indentation deformation property as a finger, can be applied to the elements coming into contact with body in the nursing-care robots or actuators.